Applied and Computational Mathematics for Digital Environments - Demidova, Liliya (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The present reprint contains the 11 papers that were accepted and published in the Special Issue "Applied and Computational Mathematics for Digital Environments" of the MDPI Mathematics journal. The topics of interest include, among others, scientific research, applied tasks, and problems in the following areas: The construction of mathematical and information models of intelligent computer systems for monitoring and controlling the parameters of digital environments; The development of intelligent optimization algorithms that search for optimal parameter values of mathematical and information models in digital environments; Software and mathematical technologies in the implementation of intelligent monitoring and computer control of the parameters of digital environments; The development and application of mathematical and information models, machine learning methods, and artificial intelligence for the analysis and processing of big data in digital environments. I hope that this reprint will be useful to those who are interested in the real-world applications of applied and computational mathematics for digital environments in terms of solving actual, practical problems in all spheres of human life and activity.